Der kranke Körper in den Tagebüchern Tobias Anton Seemans (Theatrum historiae, 2012)
Diary records made by Tobias Anton Seeman, Hofmeister of Count Franz Anton Sporck and his son-in-law, Franz Karl Swéerts-Sporck, preserved from 1726–1747, with little intervals, contain, inter alia, records of the lords’ and the writer’s ailments and their treatment. The analyses of Seeman’s references to sick bodies have led to the hypothesis that recording such information was caused by the need to compile a practical manual detailing the symptoms of diseases and their progress for the author and his master to use for a more exact recapitulation of their health condition in consultations with physicians.